(untitled) (Research, Society and Development, 2020)
Manaus is located in the north of the country and, due to geographical issues, it has little connection with other states, and even so its problems are not small. One of these obstacles is the theft of public transport that is highlighted on local social media. Violence is a notorious highlight, which shows the importance of the theme for the Amazonian who needs this means of transportation. This crime directly affects the income of the citizen, who has his goods stolen in the collective buses, which causes personal financial problems. But it is not just the pecuniary problems that are highlighted in the consequences of these acts, there are also the psychological issues that deserve focus, as they affect the mind of the oppressed and cause problems for many of those who are victims. In view of the above, data were collected, so that one could understand the criminal dynamics and propose policies to combat this type of theft. Thus, a heat map was created with the main criminal points, as well as verified the days, places, times and neighborhoods in which they occur most. Analyzing the results, it was noted that the southern and northern areas are the most affected, this being the one with the highest rates. As for the days of the week, only Sunday stands out from the others, as it has a reduction in its rate, as for the hours, a large number of night events were noted. Such issues can be a guide to be followed when carrying out future police planning to improve ostensive policing and provide security for the community in Manaus.